The Impact of Accounting Information Systems on Performance Management in the Banking Sector - Bilal Khalid; Michal Kot (My University, 2021)
This study investigated the impact of Accounting Information Systems (AIS) on performance management in Thailand’s banking sector. The study was necessitated by the need to understand the financial performance of banks in Thailand in application of advanced management techniques, business developments, growth of the current contemporary business environment and the intensive competitive business environment in the banking sector.
Keywords: Business environment; Accounting and Organizational Management